Identificação por imunoproteômica dos exoantígenos do complexo paracoccidioides, com potencial aplicação no diagnóstico e terapia da paracoccidioidomicose - Moreira, André Luís Elias (2019)
Identification by immunoproteomic of exoantigens of the Paracoccidioides complex, with potential application in diagnosis and therapy of Paracoccidioidomycosis Fungi of Paracoccidioides complex are the etiological agents of Paracoccidioidomycosis (PCM), a systemic mycosis restricted to Latin American countries. Currently, the Paracoccidioides genus is represented by P. lutzii, P. americana, P. brasiliensis, P. restrepiensis and P. venezuelensis. In some cases, oral and skin mucosal lesions caused by other pathogens may coincide with lesions caused by Paracoccidioides spp.. Moreover, even with the advances in immunological techniques used for the diagnosis of fungal diseases, false-positive results rates for PCM are present. Thus, we investigated which antigens are secreted by 4 species of the Paracoccidioides complex in order to identify and characterize new molecules, thus increasing the spectrum of antigens to be used for future diagnostic tests of PCM. Through of nanoUPLC-MSE, 79 exoantigens were identified in 4 Paracoccidioides species. In silico analysis revealed 2 exoantigens exclusive to P. lutzii species, as well as the identification of 44 unique B-cell epitopes of the Paracoccidioides complex. Thirteen exclusive epitopes distributed among Paracoccidioides species also predicted, being this excellent molecules to be employed in the future for epidemiological studies. These results demonstrate a range of epitopes exclusive to the Paracoccidioides complex as well as the identification of molecules unique to each fungal species. In addition, these analyzes allowed the identification of new candidate biomarkers to PCM diagnosis, as well as the identification of molecules to be used as future epidemiological biomarkers.